Multiple transitions resulting from remediation and re-entry of first-year undergraduate medical students: expectations and experiences, emotions and recommendations - Tlalajoe-Mokhatla, Nokuthula (University of the Free State, 2025)
Transitioning from school to tertiary education can be daunting and overwhelming, and neither students nor institutions are necessarily prepared for these transitions. Some students may even experience multiple transitions in their academic programmes. This paper focuses on the multiple transition stages during the first year of the medical programme at the University of the Free State (UFS) in South Africa. The study aimed to determine first year undergraduate medical students’ perceptions of the multiple transitions involved in the medical programme. The research was designed as an exploratory qualitative study that used focus group discussions to obtain data. Two focus group discussions were held with 17 first-year undergraduates who had undergone multiple transitions in the first year of the medical programme. Multiple transitional stages were investigated: The first was at the start of the first year (January–-June), then six months later (July–December), and then back to the start of the first year for the second time (January–June of the following year). The analysis exposed three main themes, namely (1) expectations and experiences, (2) emotions, and (3) recommendations. These themes are explained by focusing on the participants’ perceptions and following a linear process for the multiple transition stages. Medical students who went through remediation and re-entered the first-year undergraduate programme reported that, during the initial transition, lecturers and senior students did not provide the ‘big picture’ regarding expectations in the medical programme. Instead, the shared expectations did not match their ‘real’ experiences in the programme. Furthermore, students experienced a range of emotions during the multiple transitions. In conclusion, students are accepted into medical schools such as the UFS but are underprepared for the rigours of the programme and are then exposed to multiple transitions. To ease the students’ transition, medical schools must consider designing support strategies that will enable these students to manage these transitions by attending to ‘soft determinants’, such as expectations and experiences, emotions, and contextually applying the students’ recommendations in setting up such strategies.
Keywords: Transition; Multiple multi-dimensional transitions; Medical students; Expectations; Experiences; Emotions